2020
DOI: 10.1177/0146167219897181
|View full text |Cite
|
Sign up to set email alerts
|

Putting Belonging in Context: Communal Affordances Signal Belonging in STEM

Abstract: A sense of belonging in a particular context is cued not only by the people in the role but by the affordances of the role—that is, the opportunities for goal pursuit. We investigate this role-based belonging in four studies documenting that the perceived affordances of social roles inform sense of belonging and convey known benefits of belonging. Perceiving more communal opportunities in naturalistic science, technology, engineering, and mathematic (STEM) settings was associated with heightened belon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 53 publications
2
32
0
2
Order By: Relevance
“…Perceptions that STEM careers are sexist may reflect revelations from the #metoo movement, for example, Susan Fowler's experiences at Uber (Fowler, 2017), which detailed evidence of widespread gender discrimination in STEM in the United States. However, their open‐ended responses were consistent with literature suggesting that environmental cues may undermine individuals’ sense of belonging in STEM (Belanger et al., 2020; Cheryan, Plaut, Davies, & Steele, 2009).…”
Section: Discussionsupporting
confidence: 84%
“…Perceptions that STEM careers are sexist may reflect revelations from the #metoo movement, for example, Susan Fowler's experiences at Uber (Fowler, 2017), which detailed evidence of widespread gender discrimination in STEM in the United States. However, their open‐ended responses were consistent with literature suggesting that environmental cues may undermine individuals’ sense of belonging in STEM (Belanger et al., 2020; Cheryan, Plaut, Davies, & Steele, 2009).…”
Section: Discussionsupporting
confidence: 84%
“…Students who recalled science and math classrooms with more helping behaviors perceived STEM careers as affording communal goals, and in turn expressed greater interest in pursuing STEM careers (Fuesting et al, 2017). Similar effects emerged among presenters at a Women and Science Day who spontaneously varied in their emphasis on whether their scientific work included working with or helping others (Belanger et al., 2020). When middle school girls perceived that presenters focused more on communal aspects of their work, they reported more interest in pursuing science careers.…”
Section: Introductionmentioning
confidence: 81%
“…As changing stereotypes has been shown to be quite difficult (Heilman and Caleo, 2018), another fruitful road to gender equality in STEM in Germany and Japan is to reduce role and goal incongruity. An intervention to change communal goal affordances (i.e., the opportunities for goal pursuit) in STEM (Belanger et al, 2020) showed that perceiving communal goal affordances (e.g., collaborative lab activities) in STEM increased social belonging and interest, especially for women. Highlighting STEM's potential to afford communal goals might therefore alleviate goal incongruity and reduce gender-science stereotypes and backlash effects for women, because STEM is perceived as less incongruent with the female gender role.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%